Rude talk in Athens : ancient rivals, the birth of comedy, and a writer's journey through Greece - Smith, Mark Haskell (The Unnamed Press, 2021)
In ancient Athens, thousands would attend theatre festivals that turned writing into a fierce battle for fame, money, and laughably large trophies. While the tragedies earned artistic respect, it was the comedies--the raunchy jokes, vulgar innuendo, outrageous invention, and barbed political commentary--that captured the imagination of the city. The writers of these comedic plays feuded openly, insulting one another from the stage, each production more inventive and outlandish than the last, as they tried to win first prize. Of these writers, only the work of Aristophanes has survived and it's only through his plays that we know about his peers: Cratinus, the great lush; Eupolis, the copycat; and Ariphrades, the sexual deviant. It might have been the golden age of Democracy, but for comic playwrights, it was the age of Rude Talk. Watching a production of an Aristophanes play in 2019 CE and seeing the audience laugh uproariously at every joke, Mark Haskell Smith began to wonder: what does it tell us about society and humanity that these ancient punchlines still land? When insults and jokes made thousands of years ago continue to be both offensive and still make us laugh? Through conversations with historians, politicians, and other writers, the always witty and effusive Smith embarks on a personal mission (bordering on obsession) exploring the life of one of these unknown writers, and how comedy challenged the patriarchy, the military, and the powers that be, both then and now. A comic writer himself and author of many books and screenplays, Smith also looks back at his own career, his love for the uniquely dynamic city of Athens, and what it means for a writer to leave a legacy.